A Multi-step Approach to Adapting a Mind-Body Resiliency Intervention for Fear of Cancer Recurrence and Uncertainty in Survivorship (IN FOCUS). (18th February 2022) - Hall, Daniel L.; Yeh, Gloria Y.; O'Cleirigh, Conall; Peppercorn, Jeffrey; Wagner, Lynne I.; Denninger, John; Bullock, Andrea J.; Mizrach, Helen R.; Goshe, Brett; Cheung, Tina; Li, Raissa; Markowitz, Alexandros; et al.
Background: For cancer survivors, there is a paucity of fear of recurrence (FOR) interventions that integrate empirically supported mind-body and psychological skills for managing FOR and are delivered in scalable formats. Objective: To adapt an evidence-based resiliency intervention to address FOR among cancer survivors. Methods: A multidisciplinary team of researchers, clinicians, and patient stakeholders followed an iterative intervention adaptation process (ORBIT). In Step 1, we sought to define key FOR management skills through a literature review and feedback from stakeholders. In Step 2, we integrated findings into a treatment manual and refined procedures for in-person delivery to groups of cancer survivors, defined as adults who had completed primary cancer treatment for non-metastatic cancer. In Step 3, we conducted a single arm trial to assess initial acceptability and change in FOR severity with 23 cancer survivors (N=4 intervention groups). In Step 4, we conducted additional qualitative interviews with 28 cancer survivors (N=6 focus groups stratified by FOR severity, N=15 individual interviews) to define adaptive and maladaptive strategies for coping with FOR and to identify preferences for delivery. In Step 5, we refined the treatment manual and procedures for testing in a future pilot randomized feasibility trial. Results: We identified critical feedback using a combination of qualitative and quantitative methods. The single arm trial suggested preliminary feasibility and sustained reductions in FOR severity, yet need for refinement (i.e., eligibility, delivery modality), prompting additional qualitative interviews for further targeting. The resulting intervention (IN FOCUS) is comprised of virtual, synchronous, group-delivered sessions that offer an integrated approach to FOR management by teaching cognitive-behavioral techniques, meditation, relaxation training, adaptive health behaviors, and positive psychology skills. Sessions are targeted by applying skills to FOR and associated healthcare engagement. Conclusions: IN FOCUS is a targeted intervention for teaching mind-body resiliency skills to groups of cancer survivors with elevated FOR. Next steps are testing feasibility in a pilot randomized trial.